Crown cover of native trees in the structural development of reforestations in Rondônia - Bentes, Michelliny Pinheiro de Matos; Rocha, Rodrigo Barros; Almeida, Ana Luma Caldas (Revista Ceres, 2017)
The objective of this study was to assess the initial development of a reforestation structure using the crown projection method as an indicator to monitor the recovery in degraded areas in the State of Rondônia. The method consisted of correlating canopy projection data with structural performance variables of six native tree species of the Amazon region. The study found that the species “large acacia” had the best capacity to promote shading, favor rapid covering, protection, and stabilization of the soil in the initial phase, at 24 months, with a crown area of 62.82 m². The crown projection method was suitable to identify the native trees that stand out in the initial years of restoration of degraded areas. The method can be used to indicate variations in the structural development of species as a function of site quality and to assist in determining the feasibility of native tree species selected for reforestation. Therefore, further studies on this approach are needed to develop models of crown cover prediction and validate crown cover as an indicator of reforestation development in restoration processes in the Amazon region.